ANTIMICROBIAL ACTIVITY OF METHANOL EXTRACTS OF SOME TRADITIONAL MEDICINAL PLANTS FROM TAMIL NADU, INDIA - V.A.KINSALIN; P.SARAVANA KUMAR; V.DURAIPANDIYAN; S.IGNACIMUTHU; N.A.AL-DHABI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: We assessed the antimicrobial activity of methanol extracts of 4 medicinal plants against human pathogenic Gram positive and Gram negative bacteria and fungi. Four medicinal plants namely Terminalia arjuna(bark), Butea monosperma(bark), Mollugo nudicaulis(whole plant), Evolvulus alsinoides(whole plant) were collected from different places in Tamil Nadu, India. Methods: Methanol extracts of these plants were assessed for antimicrobial activity using disc diffusion method at 5mg/disc and 10mg/disc. Minimum inhibitory concentration (MIC) and phytochemical analysis were also determined. Results: Methanol extract inhibited the growth of bacterial and fungal strains. Minimum inhibitory concentration (MIC) of T.arjuna (bark) methanol extract was 500mg/ml against Gram positive and Gram negative bacteria. The MIC of B.monosperma (bark) methanol extract was 250mg/ml against fungi. The phytochemical analysis of methanol extracts of T.arjuna and B.monosperma showed the presence of glycosides, flavinoids, steroids and tannins. T.arjuna and B.monosperma showed good antimicrobial activity. Conclusion: It can be concluded that the methanol extract possesses potent bactericidal and fungicidal activity which in turn may be due to the presence of biologically active ingredients with antimicrobial activity in the medicinal plants. Keywords; Antibacterial, Antifungal, Terminalia arjuna, Butea monosperma, Minimum inhibitory concentration (MIC)